Evolution and the social sciences - Dunbar, R (Sage, 2007)
When the social sciences parted company from evolutionary biology almost exactly a century ago, they did so at a time when evolutionary biology was still very much in its infancy and many key issues were unresolved. As as result, the social sciences took away with them an understanding of evolution that was in fact based on 18th - rather than 19th-century biology. I argue that contemporary evolutionary thinking has much more to offer the social sciences than most people have assumed. Contemporary evolutionary research on human behaviour focuses on two main issues at the micro-social scale: understanding the trade offs in individual decision-making and understanding the cognitive constraints that limit flexibility of decisions. I offer examples of both these approaches. Finally, I consider the broader question of the macro-social scale.